MALAY ETHICS IN ABSTINENCE FROM PROHIBITION: A META-ANALYSIS - Rina Ari Rohmah; Purwantoro (CV.Karoteh Utama, 2023)
Abstinence is a type of verbal discipline that is used as a foundation for achieving social welfare by the majority of the Malay community. This research will look into Malay abstinence ethics. Nine previous journal articles were analyzed and presented in a meta-analysis study, revealing Malay ethics in abstinence. Meta-analysis is the study of a number of previous research results on similar problem topics in order to determine the results and conclusions of previous research. Purposive sampling was used to select research based on criteria such as suitability for the research topic discussed, articles published between 2012 and 2022, and articles published in accredited journals. To determine the outcomes of previous studies' narrative research, quantitative data analysis with percentages and qualitative data analysis were used. According to the study's findings, Malay ethics can be achieved by implementing abstinence in everyday life based on the problems encountered, because abstinence varies in various fields of life such as religion, education, custom, economy, and health.